PREDIKSI KEJADIAN PENYAKIT TUBERKULOSIS PARU MENGGUNAKAN METODE PERAMALAN MOVING AVERAGE DAN DEKOMPOSISI TIME SERIES - Novanda, Dicky; Hidayati, Rahmatina (Universitas Islam Balitar, 2024)
Abstract: Indonesia is the third country with the largest number of deaths due to pulmonary tuberculosis infection. In order to suppress the spread of tuberculosis in Indonesia, in 2021 the government launched a tuberculosis control program which aims to prevent and reduce the spread. One effort to assess whether the program that has been implemented is operating well or not is to forecast the incidence of pulmonary tuberculosis. This research aims to predict the incidence of pulmonary tuberculosis to provide useful information for health workers and related parties in efforts to prevent and control pulmonary tuberculosis at Hospital X, Malang City in 2024. The method that will be used to predict the number of tuberculosis sufferers is a moving average. and time series decomposition. The multipicative decomposition method produces the smallest MAPE, namely 15.37%, which is in the good category compared to additive and moving average decomposition. In 2022 and 2023 there will be a significant spike in pulmonary tuberculosis cases at Hospital X Malang City and men have a higher risk factor than women. Most cases of pulmonary tuberculosis infection occur in the elderly (46-65 years) and adults (26-45 years) age groups.